POTENTIAL OF NASAL AND ORAL SPRAYS OF ALLYL DISULFIDE GARLIC EXTRACT AS PROTECTION AGAINST SARS-COV-2 - Silvia Vera Indrawati; Salwa Febria Monica; Iftitah Nabiilah Ramadhani; Siska Nurlivia; Azka Putri Anisa; Islamy Rahma Hutami (Odonto : Dental Journal, 2022)
Background: Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2), a virus that causes COVID-19 disease, occurred in 2019. The prevalence of COVID-19 was increasing and spreading rapidly in several countries including Indonesia. Some efforts have been proposed to reduce the coronavirus outbreak, which is the exploration potentials inhibitor of SARS-CoV-2, vaccination, and improving health protocols by implementing 5M. This study characterized several formulations of nasal spray and evaluated their biological function as antivirus.Method: The garlic was used in this study, crude extract performed by garlic extraction using maseration and evaporated using rotary evaporator. The garlic crude extract was prepared to make nasal and oral sprayer agent and evaluated using thin layer chromatography. Nasal and oral spray composition was modelled and docked with spike glycoprotein of SARS-CoV-2 and angiotensin converting enzyme-2 (ACE-2). Garlic extract showed containing allyl sulfide as bioactive compound in garlic, which was detected at Rf 0.5. biological functions revealed that the component of nasal and oral spray have antiviral agents and block the spike glycoprotein – ACE2 interaction.Result: The allyl disulfide complex detected several active amino acid residues, both with the spike glycoprotein protein and the ACE2 receptor. Conclusion: This study suggested that the nasal and oral spray garlic has the potential as an antiviral, especially inhibiting the interaction between ACE2 and spike glycoprotein. Further in vitro and in vivo studies are required for advance investigation.